Mobile Marketing: Pengaruh Aspek Kepercayaan Diri, Kepercayaan Institusi dan Kontrol Diri Pengguna - Diki Gita Purnama (Universitas Paramadina, 2016)
AbstractThis study analyzed the consumer behavior using mobile phone marketing. The growth of mobile marketing usage was increasing in Indonesia. This gave the opportunity for marketers to use this technology to capture and to maintain consumers in the long-term period. This study aimed at analyzing the consumer behavior to use mobile marketing as the recipients of information. The study used the institutional trust, personal trust, perceived control. These variables were analyzed using survey to a number of respondents. The respondents were workers and students. The total number was 83. The sampling uses non-probability sampling, namely purposive sampling. The data was analyzed using multiple regression statistics. The managerial implications were explored to provide vivid understanding about the usage of mobile marketing in Indonesia. Only personal trust had positive correlation with consumer behavior to use mobile marketing.